Treatment of Neuroendocrine Tumors (NETs) Using Somatostatin Analogs: Current View, Clinical Achievements and Future Perspectives - Wongso, Hendris (Indonesian Journal of Cancer Chemoprevention, 2019)
Neuroendocrine tumors (NETs), previously known as carcinoid tumors, are a heterogeneous group of neoplasms which originate from cells of the endocrine or nervous system with an overall incidence of 1–5 cases per 100,000 individuals per year. Recent studies showed that their incidence has dramatically increased worldwide over the last few years. The majority of NETs overexpress the somatostatin receptors (SSTRs) in tumor cells which are further being used as the important targets for therapy purposes using somatostatin analogs (SSAs) such as octreotide and lanreotide. Like native somatostatin, SSAs bind to SSTRs and induce a range of cellular effects, including antitumor activity. Antitumor activity of SSAs and their high binding properties for the SSTRs have become valuable tools for developing advanced treatment of NETs. Consequently, SSAs have been used widely in routine clinical practice, especially for treatment of various types of NETs. Despite treatment using SSAs have made a positive contribution, recent development suggests that the used of SSAs in combination with chemotherapy or peptide receptor radionuclide therapy (PRRT) can improve clinical outcome in patients with NETs. This review provides an overview of recent trend in the treatment of NETs using SSAs, their clinical achievements in the last few years and their potential applications in the future.Keywords: neuroendocrine tumors, treatment, somatostatin analogs, chemotherapy, PRRTNeuroendocrine tumors (NETs), previously known as carcinoid tumors, are a heterogeneous group of neoplasms which originate from cells of the endocrine or nervous system with an overall incidence of 1–5 cases per 100,000 individuals per year. Recent studies showed that their incidence has dramatically increased worldwide over the last few years. The majority of NETs overexpress the somatostatin receptors (SSTRs) in tumor cells which are further being used as the important targets for therapy purposes using somatostatin analogs (SSAs) such as octreotide and lanreotide. Like native somatostatin, SSAs bind to SSTRs and induce a range of cellular effects, including antitumor activity. Antitumor activity of SSAs and their high binding properties for the SSTRs have become valuable tools for developing advanced treatment of NETs. Consequently, SSAs have been used widely in routine clinical practice, especially for treatment of various types of NETs. Despite treatment using SSAs have made a positive contribution, recent development suggests that the used of SSAs in combination with chemotherapy or peptide receptor radionuclide therapy (PRRT) can improve clinical outcome in patients with NETs. This review provides an overview of recent trend in the treatment of NETs using SSAs, their clinical achievements in the last few years and their potential applications in the future.Keywords: neuroendocrine tumors, treatment, somatostatin analogs, chemotherapy, PRRT